Surveillance of Nipah virus in Pteropus medius of Kerala state, India, 2023 - Balasubramanian, R.; Mohandas, Sreelekshmy; Thankappan, Ullas P.; Shete, Anita; Patil, Dilip; Sabarinath, Kannan; Mathapati, Basavaraj; Sahay, Rima; Patil, Deepak; Yadav, Pragya D. (Frontiers in Microbiology, 2024)
Since the year 2018, the Kerala state of India has reported four Nipah virus (NiV) disease outbreaks which raised concerns about Nipah virus spillover from bats to the human population. Considering this, a cross-sectional study was undertaken in the Pteropus medius bat population around the Nipah virus-affected regions of Kozhikode, Kerala, India during February, July, and September months of the year 2023. Throat swabs, rectal swabs, and organ samples were collected from bats to test for Nipah virus by real-time RT-PCR, while serum samples were screened for anti-Nipah IgG antibodies through ELISA. An overall seroprevalence of 20.9% was observed in 272 P. medius bats tested. The throat and rectal swab samples of 321 bats were negative for NiV RNA. However, four out of 44 P. medius bats tested positive for NiV in their liver/spleen samples. The partial N gene retrieved showed more than 99% similarity with the earlier reported NiV genome from Kerala state, India. The findings of the study give the caution that the spillover risk exists in the region and necessary precautions should be taken.